Implementasi Model-Model Pembelajaran Pada Mata Pelajaran Pendidikan Agama Islam Di SMAN 2 Garut - Rohim, Saepul; Helmi, Helmi; Ardiawan, Ismal; Herdiana, Nana; Holik, Abdul (MASAGI : Jurnal Pendidikan Agama Islam, 2024)
Abstract The learning Model is one of the important parts in the learning process. Where there are many factors that become obstacles in the learning process where teachers must be able to prepare various devices in the process. Many factors that affect the low interest of students in learning PAI, among other factors of the teacher itself, for example, in the learning process activities, approaches, strategies, methods or learning models are still conventional, learning tends to be focused on the teacher (Teacher Centered). The method used in this study is qualitative research in which the presentation of data in a descriptive qualitative sourced from references or observations that have been made. The place of research in SMAN 2 Garut which aims to explore the learning model used in the learning process in PAI subjects. The results of research conducted that PAI teachers at SMAN 2 Garut diverse in using learning models. The number of PAI teachers in the school is three and varies in understanding and using learning models in achieving learning goals. There are those who use the learning model of Active Learning, Cooperative Learning, contextual. All of which have an effect on increasing student motivation. Keywords: Learning Model, Islamic Religious Education Learning Mo